2020
DOI: 10.1021/acscatal.0c04656
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Oxygen Evolution Reaction Activity Achieved Using Ir Single Atoms on Amorphous CoOx Nanosheets

Abstract: Developing efficient electrocatalysts for an oxygen evolution reaction (OER) is important for renewable energy storage. Here, we design high-density Ir single-atom catalysts supported by CoO x amorphous nanosheets (ANSs) for the OER. Experimental results show that Ir single atoms are anchored by abundant surface-absorbed O in CoO x ANSs. Ir single-atom catalysts possess ultrahigh mass activity that is 160-fold of commercial IrO 2 . The OER of IrCoO x ANSs reached a record low onset overpotential of less than 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 43 publications
(71 reference statements)
1
118
0
Order By: Relevance
“…X‐ray absorption near‐edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS) measurements were further carried out for obtaining more information about the electronic structures and atomic coordination environments of the Ir@IrNiO samples. As shown from the Ir L 3 ‐edge XANES spectra (Figure 3c), the white‐line peak position of Ir@IrNiO is a little left‐shifted compared with the reference IrO 2 , suggesting that the total oxidation state of Ir is lower than +4, [ 19,41,44,45 ] and this consistent with the above XPS result. It has been reported that the white line intensity is thought to be proportional to the d orbital density of states, which can be affected by the multiple oxidization states, [ 19 ] and thus, the relatively low white line intensity further confirms the mixed valences of the Ir.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…X‐ray absorption near‐edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS) measurements were further carried out for obtaining more information about the electronic structures and atomic coordination environments of the Ir@IrNiO samples. As shown from the Ir L 3 ‐edge XANES spectra (Figure 3c), the white‐line peak position of Ir@IrNiO is a little left‐shifted compared with the reference IrO 2 , suggesting that the total oxidation state of Ir is lower than +4, [ 19,41,44,45 ] and this consistent with the above XPS result. It has been reported that the white line intensity is thought to be proportional to the d orbital density of states, which can be affected by the multiple oxidization states, [ 19 ] and thus, the relatively low white line intensity further confirms the mixed valences of the Ir.…”
Section: Resultssupporting
confidence: 81%
“…As shown in Figure S9 in the Supporting Information, the Ir 4f XPS curves of the Ir–NiO samples also exhibit obvious differences. All the samples show two peaks at 61.7 and 64.7 eV, which are assigned to Ir 4+ 4f 7/2 and 4f 5/2 , [ 19,39–43 ] respectively; however, for the two samples of Ir 3.9 –NiO (Ir@IrNiO) and Ir 5.1 –NiO, there are two more peaks at ≈60.6 and 63.6 eV assigned to metallic Ir 0 4f 7/2 and 4f 5/2 , [ 42 ] respectively. These results suggest that one part of the added Ir exists in the form of Ir 4+ doped into the NiO lattice, and the other part is the loaded Ir particles, confirming the above TEM images (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…We further investigate the material structure of the catalyst by synchrotron X-ray absorption spectra. [35][36][37] The extended X-ray absorption fine structure (EXAFS) spectra and their wavelet transform analyses (Figure 3a-b, S11, and Table S1 ) showed To prove the enhanced H2O adsorption/dissociation ability on Ru/MoO2, we carried out Fourier transfer infrared spectrum (FTIR) and H2O adsorption tests. Figure 3e reports FTIR spectra, in which Ru/MoO2 shows the strongest hydroxyl response signal among those of MoO2 and Ru, in the range between 2900 cm -1 ~ 3500 cm -1 .…”
Section: Introductionmentioning
confidence: 99%
“…The alloy composition and the distribution of Ti, Zr, Hf and Nb elements were analyzed using EDS. The crystal structures of Ti 0.20 Zr 0.20 Hf 0.20 Nb 0.40 HEA and its hydrides were determined by XRD [43] (PANalytical B.V., Almelo, The Netherlands), using an X'Pert PRO MPD working at 40 kV and 40 mA. The typical scanning parameters are 25-90 • in 2θ, 0.013 • in step size and 0.4 s in count time.…”
Section: Sample Characterizationmentioning
confidence: 99%